Who will Help in Situations of Intimate Partner Violence: Exploring Personal Attitudes and Bystander Behaviours - Lazarus, Kathryn; Signal, Tania (International Journal of Criminology and Sociology, 2013)
<!-- [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> <!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]--> Intimate partner violence (IPV) continues to be a problem within society, with many studies focusing on general attitudes toward violence against women as a gauge of positive societal change in this area. To investigate whether individual personal attitudes toward violence against women were predictive of prosocial bystander behaviours in situations of IPV, 157 Australian community members completed an online survey. This survey investigated the factors of bystander intention, bystander self-efficacy, general and privacy attitudes toward violence against women, fear of intervening and the effects/impact of psychological abuse as predictors of willingness to intervene in IPV situations. Bystander intention, self-efficacy and gender were significantly associated with willingness to intervene, whilst respondent’s attitudes toward violence against women was not. The implications of these findings for promoting social control and bystander intervention in situations of IPV are discussed. <span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-AU; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">